LONELINESS AND HEALTH: A CRITICAL REVIEW OF THE EPIDEMIOLOGICAL EVIDENCE. (11th November 2018) - Valtorta, N; Hanratty, B
Abstract: Is the depiction of loneliness as a public health issue evidence-based? In this presentation, we critically review the epidemiological literature linking the subjective feeling of loneliness (as opposed to the more objective situation of social isolation) to morbidity and mortality. Using a) the 'Grades of Recommendation, Assessment, Development, and Evaluation' guidance and b) Gordis' guidelines for assessing evidence of causation, we assess the quality of the evidence across physical and mental health outcomes, and across different study designs and populations. This process allows us to consider the main challenges facing epidemiologists, which include: disentangling the direction of causality; distinguishing between confounding, mediating and moderating factors; and identifying at-risk groups and opportunities for intervention. We will discuss the implications of uncertainty in the field for users of evidence (campaigners, policy-makers, practitioners and other stakeholders), and will conclude the presentation with suggestions for how me might strengthen the evidence base.